The Burden of Attention-Deficit/Hyperactivity Disorder Traits in Adult Patients with Major Depressive Disorder in Japan - Kato M; Tsuda H; Chen Y; Tsuji T; Nishigaki N (Neuropsychiatric Disease and Treatment, 2023)
Masaki Kato,1,* Hiroshi Tsuda,2– 5,* Yirong Chen,6 Toshinaga Tsuji,7 Nobuhiro Nishigaki2 1Department of Neuropsychiatry, Kansai Medical University, Osaka, Japan; 2Japan Medical Office, Takeda Pharmaceutical Company Limited, Tokyo, Japan; 3Department of Neurology, Juntendo University Faculty of Medicine, Tokyo, Japan; 4Department of Neurology, Toho University Faculty of Medicine, Tokyo, Japan; 5Clinical Research, Innovation and Education Center, Tohoku University, Sendai, Japan; 6Cerner Enviza, Singapore, Singapore; 7Medical Affairs Department, Shionogi & Co. Ltd, Osaka, Japan*These authors contributed equally to this workCorrespondence: Nobuhiro Nishigaki, Japan Medical Office, Takeda Pharmaceutical Company Limited, 1-1, Nihonbashi-Honcho 2-Chome, Chuo-Ku, Tokyo, 103-8668, Japan, Tel +81-80-9305-2077, Fax +81-3-3278-2925, Email nobuhiro.nishigaki@takeda.comPurpose: Symptoms of attention-deficit/hyperactivity disorder (ADHD) often overlap with and are hidden by those of mood disorders, including major depressive disorder (MDD), resulting in adult ADHD patients being misdiagnosed as MDD. This study aims to examine if diagnosed MDD patients are more likely to exhibit ADHD traits and if the presence of ADHD traits increases the humanistic burden, including the impairment of health-related quality of life (HRQoL), work productivity and activity impairment (WPAI), and health-care resource utilization (HRU), on MDD patients in Japan.Methods: This study utilized existing National Health and Wellness Survey (NHWS) data. The 2016 Japan NHWS is an internet-based survey comprising a total of 39,000 respondents, including those with MDD and/or ADHD. A randomly selected subset of the respondents responded to the Japanese-version Adult ADHD self-report scale (ASRS-v1.1; ASRS-J) symptom checklist. Respondents were considered ASRS-J-positive if the total score was ≥ 36. The HRQoL, WPAI, and HRU were assessed.Results: Among MDD patients (n = 267), 19.9% were screened ASRS-J-positive, while 4.0% of non-MDD respondents (n = 8885) were ASRS-J-positive. There was a significant association between MDD status and ASRS-J status (crude odds-ratio [OR]: 5.9) as well as between MDD status and ADHD-diagnosis status (crude OR: 22.6). MDD patients who were ASRS-J positive experienced significantly lower HRQoL and higher WPAI than those who were ASRS-J negative. Limitations of this study include potential recall bias owing to the self-report nature of the survey and lack of objective confirmation of MDD diagnosis through review of medical records.Conclusion: This study demonstrated a significant association between MDD status and exhibiting ADHD traits. Adult MDD patients screened ASRS-J-positive experienced significantly higher humanistic burden than patients screened ASRS-J-negative. Our results emphasize the importance of ensuring appropriate screening of ADHD and looking out for potentially hidden ADHD symptoms when diagnosing and treating MDD in adulthood.Keywords: attention-deficit/hyperactivity disorder, web-based survey, major depressive disorder, undiagnosed ADHD, humanistic burden